2018
DOI: 10.3389/fpsyg.2018.00421
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Cross-Cultural Comparison of Adult Playfulness in Mainland China and German-Speaking Countries

Abstract: Compared with playfulness in infants and children, playfulness in adults is relatively under-studied. Although there is no empirical research comparing differences in adult playfulness across cultures, one might expect variations between Western and Eastern societies such as China. While playfulness is typically seen as a positive trait in Western culture, there are hints in Chinese culture that being playful has negative connotations (e.g., associations with laziness and seeing play as the opposite of work). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…This interrelatedness causes them to take serious consideration of their parents’ and teachers’ expectations. The students also feel that they need to try to do their best work because of the intense competition in the Chinese education system (Pang & Proyer, ). In such a cultural environment, developing personal ICT interests must serve test‐oriented goals.…”
Section: Discussionmentioning
confidence: 99%
“…This interrelatedness causes them to take serious consideration of their parents’ and teachers’ expectations. The students also feel that they need to try to do their best work because of the intense competition in the Chinese education system (Pang & Proyer, ). In such a cultural environment, developing personal ICT interests must serve test‐oriented goals.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Lieberman (1965 , 1966 ) was one of the first to shift attention from the activity to the participant , thus attempting to define playfulness as a character trait, with sub-traits such as cognitive spontaneity, physical spontaneity, social spontaneity, manifest joy and sense of humor (for recent work on this see Glynn and Webster, 1992 ; Proyer, 2012 ; Shen et al, 2014 ; see also Barnett, 2017 for a culture comparative approach).…”
Section: Introductionmentioning
confidence: 99%
“…While the results of the first three characteristics support the hypotheses, the significant difference regarding adult playfulness is revealing. It may be considered a complement to international adult playfulness and gamification research (Pang & Proyer, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the only available cross-country study on adult playfulness, Pang and Proyer ( 2018 ) concluded that societal rules and cultural factors might affect playfulness in a society. Anecdotal evidence suggests the Danish culture is more liberal and progressive than many other cultures, including the German culture (Allen, 2012 ; Hoefler & Vejlgaard, 2011 ; Jensen, 2017 ).…”
Section: Theoretical Foundations and Hypothesis Developmentmentioning
confidence: 99%